Spatiotemporal assessment of particulate matter (PM10 and PM2.5) and ozone in a Caribbean urban coastal city - Duarte, Ana L. (2021)
Air pollution has become a critical issue in urban areas, so a broad understanding of its spatiotemporal characteristics is important to develop public policies. This study analyzes the spatiotemporal variation of atmospheric particulate matter (PM10 and PM2.5) and ozone (O3) in Barranquilla, Colombia from March 2018 to June 2019 in three monitoring stations. The average concentrations observed for the Móvil, Policía, and Tres Avemarías stations, respectively, for PM10: 46.4, 51.4, and 39.7 µg/m3; for PM2.5: 16.1, 18.1, and 15.1 µg/m3 and for O3: 35.0, 26.6, and 33.6 µg/m3. The results indicated spatial and temporal variations between the stations and the pollutants evaluated. The highest PM concentrations were observed in the southern part of the city, while for ozone, higher concentrations were observed in the north. These variations are mainly associated with the influence of local sources in the environment of each site evaluated as well as the meteorological conditions and transport patterns of the study area. This study also verified the existence of differences in the concentrations of the studied pollutants between the dry and rainy seasons and the contribution of local sources as biomass burnings from the Isla Salamanca Natural Park and long-range transport of dust particles from the Sahara Desert. This study provides a scientific baseline for understanding air quality in the city, which enables policy makers to adopt efficient measures that jointly prevent and control pollution.